Controlled synthesis and improved stability of SiC nanoparticles under varying conditions: combined experimental and theoretical bandgap engineering - Esmael, Mahira Muhsen; Omar, Mustafa Saeed; Dagdelen, Fethi (Taylor & Francis Ltd, 2026)
Silicon carbide nanoparticles (SiC NPs) were synthesized via pulsed Nd: YAG laser ablation of a SiC target in deionized water. With the effects of laser fluence, wavelength and ablation time, a 2.51-12.78 nm size range of nanoparticles was produced. This size range yields an energy gap of 4.74-3.19 eV. FTIR confirmed SiC formation through characteristic bands in the 400-900 cm(-)(1) region, coupled with Si-O-Si and O-H groups formed by partial surface oxidation, while XRD identified the crystalline 6H-SiC polytype. The most stable colloids were obtained at 1064 nm and 4.7 J/cm(2). EDS verified the presence of Si, C and O. The size-dependent band gap behavior aligned with quantum confinement theory. Overall, the study demonstrates that tuning laser parameters enables controlled synthesis and improved stability of SiC NPs for advanced nanomaterial applications.
Keywords: SiC; Nd-YAG; laser synthesis; PLAL; nanoparticles; stability